Ninja Xpress Digital Communication as a Marketing Communication and Information Publication Tool - Haura Putri Aqillah; Suheri Harahap (CV. AFDIFAL MAJU BERKAH, 2026)
The development of digital technology has transformed corporate communication patterns, making them more flexible, interactive, and integrated, including in marketing communication, which now requires strategic management of digital channels to ensure consistent messaging and strong relationships with the public. This research analyzes Ninja Xpress's digital communication as a means of marketing communication and information dissemination, based on Don E. Schultz's Integrated Marketing Communication (IMC) perspective. The study uses a descriptive qualitative method through observation of digital channels (website, Instagram, TikTok, Facebook, and YouTube) along with a literature review, referring to IMC concepts that emphasize message integration, communication consistency, and relationship-building with audiences. The findings show that Ninja Xpress utilizes various digital channels with distinct functions while maintaining a consistent core message, namely ease of logistics services, support for MSMEs, domestic and international delivery reach, and technology utilization. Digital media are also used to build public relations through customer service, social media interaction, and educational content. However, responses to several customer complaints still tend to rely on generic templates, which do not always provide specific solutions. Overall, Ninja Xpress's digital communication has supported the implementation of IMC principles in strengthening brand image and public relations. The company is advised to improve the quality of digital interactions through more personal, solution-oriented responses focused on resolving customer issues.